Increased plasma renin by vasodilators promotes the progression of abdominal aortic aneurysm - Liu, Yu; Liu, Shuai; Zhao, Jiani; Wu, Kemin; Xu, Baohui; Wang, Wei (Frontiers in Pharmacology, 2023)
Abstract Background It is well-accepted that antihypertensive therapy is the cornerstone of treatment for abdominal aortic aneurysms (AAA) patients with hypertension. Direct-acting vasodilators were used in the treatment of hypertension by directly relaxing vascular smooth muscle, but may have destructive effects on the aortic wall by activating the RAS axis. Their roles in AAA disease remain to be elucidated. In this study, we employed hydralazine and minoxidil, two classical direct-acting vasodilators, to investigate their influence and potential mechanisms on AAA disease. Methods and Results In this study, we investigated the plasma renin level and plasma renin activity in AAA patients. Simultaneously, age and gender ratio-matched patients diagnosed with peripheral artery disease and varicose veins were selected as the control group using a ratio of 1:1:1. Our regression analysis suggested both plasma renin level and plasma renin activity are positively associated with AAA development. In view of the well-established relationship between direct-acting vasodilators and increased plasma renin, we established a porcine pancreatic elastase-infused AAA mouse model followed by oral administration of hydralazine (250mg/L) and minoxidil (120mg/L) to investigate effects of direct-acting vasodilators on AAA disease. Our results suggested both hydralazine and minoxidil promoted the progression of AAA with increased aortic degeneration. Mechanistically, the vasodilators aggravated aortic inflammation by increased leukocytes infiltration and inflammatory cytokines secretion Conclusions and relevance Plasma renin level and plasma renin activity are positively associated with AAA development. Direct vasodilators aggravated experimental AAA progression, which raised cautionary concerns about its applications in AAA disease.